PENGARUH PENGGUNAAN MEDIA GAME INTERAKTIF BERBASIS WORDWALL TERHADAP HASIL BELAJAR MATA PELAJARAN SBDP SISWA KELAS V SD NEGERI 004 SAMBUTAN TAHUN PEMBELAJARAN 2024/2025 - Rabiatul Adawiyah; Muhlis; Muhammad Ramli Buhari; Yudo Dwiyono; Sukriadi; Hety Diana Septika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Instructional media plays a vital role in helping students understand learning materials in a more enjoyable and meaningful way. The use of interactive game-based media such as Wordwall is one innovation that can increase students' motivation and learning outcomes. This study was motivated by the low learning achievement of fifth-grade students at SD Negeri 004 Sambutan in the SBdP (Art and Culture) subject. The aim of this study is to determine the effect of using interactive game-based media with Wordwall on students’ learning outcomes in the topic of recognizing various decorative patterns from different regions of Indonesia. This research employed a quantitative approach using a Quasi-Experimental method with a Nonequivalent Control Group Design. The population consisted of all fifth-grade students, totaling 73, with class V B as the control group and class V C as the experimental group. Data collection techniques included observation, testing, and documentation, using instruments such as pretest and posttest sheets and documentation guidelines. Data analysis techniques involved normality tests, homogeneity tests, N-Gain tests, and hypothesis testing using a T-Test. The results of the hypothesis testing showed an Asymp.Sig. (2-tailed) value of 0.000, which is less than 0.05. Based on the decision rule of the T-Test, this result indicates a statistically significant difference between the experimental and control groups. Therefore, it can be concluded that the use of interactive game-based media using Wordwall has a significant effect on improving the learning outcomes of fifth-grade students at SD Negeri 004 Sambutan in the 2024/2025 academic year.